IMPLEMENTASI SISTEM PENDIDIKAN ISLAM DI ERA TURKI UTSMANI - Neneng Fauziah; Rumbang Sirojudin; Nanang Faturachman; Wasehudin Wasehudin; Fandy Adpen Lazzavietamsi (Tarbiyatuna Kajian Pendidikan Islam, 2024)
The Ottoman Turkish dynasty was a period of Islamic revival. The Ottomans carried out massive expansion in spreading Islam and bringing about a golden age again. This of course cannot be separated from the influence of education at that time. This research aims to reveal the history of Ottoman Türkiye and the implementation of the Islamic education system during that time. Using the qualitative method of historical perspective, the author carries out the stages of determining research topics, heuristics, criticism and historiography to analyze and describe the results from various books, literature, documents and related writings. The research results show that; 1). The Ottoman Caliphate was founded by the Oghuz tribe led by Erteghul. After Erteghul died, the leadership continued by Caliph Uthman bin Ertoghul (1290 AD-1326 AD) began the period of Islamic revival by expanding several areas and establishing madrasas. 2). The implementation of education in the expansion phase emphasized the spread of Islam by establishing madrasas in every territory. The curriculum used is only the Islamic religious curriculum and the method of memorizing books. Meanwhile, in the golden phase of the Islamic education system, the emphasis was on commitment to developing Islamic education and science, improving the quality of teachers, making Istanbul a center of knowledge and developing Islamic architecture. In the decline phase there was a decline in the economy and politics which caused a decline in the quality of Islamic education. so that the reform of Islamic education in a modern direction emerged which refers to western education.